Higher Education in Mauritius: Challenges and Perspectives of Internationalization - Motala Timol, Shaheen; Kinser, Kevin (International Higher Education, 2017)
Since 2000, Mauritius has had a policy to become a knowledge hub, with internationalization of its higher education sector as a key initiative. The country had several difficulties in implementing this plan, and based on this experience is now reviewing its efforts and policies to address the issues encountered. This case offers several lessons to understand how an internationalization agenda can be implemented as an element of a diversified economy.